Posttraumatic stress symptoms among adults caring for orphaned children in HIV-endemic South Africa. - Kuo, C; Reddy, M; Operario, D; Cluver, L; Stein, D (Springer, 2013)
There is growing evidence that mental health is a significant issue among families affected by AIDS-related parental deaths. The current study examined posttraumatic stress symptoms and identified risk factors among adults caring for AIDS-orphaned and other-orphaned children in an HIV-endemic South African community. A representative community sample of adults caring for children (N = 1,599) was recruited from Umlazi Township. Of the 116 participants who reported that a traumatic event was still bothering them, 19 % reported clinically significant posttraumatic stress symptoms. Of the 116 participants, caregivers of AIDS-orphaned and other-orphaned children were significantly more likely to meet threshold criteria for PTSD (28 %) compared to caregivers of non-orphaned children (10 %). Household receipt of an old age pension was identified as a possible protective factor for PTSD symptoms among caregivers of orphaned children. Services are needed to address PTSD symptoms among caregivers of orphaned children.